2017
DOI: 10.5114/aoms.2016.61900
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume changes before and after glycated hemoglobin (HbA 1c ) improvement in a large study population

Abstract: IntroductionDiabetes mellitus (DM) is a metabolic disorder associated with both microvascular and macrovascular complications. Mean platelet volume (MPV) is a marker of platelet activity, which plays a major role in the development of vascular complications of DM. The aim of this study is to compare the MPV levels before and after the decrease of glycated hemoglobin (HbA1c) levels in a large diabetic population.Material and methodsThis was a retrospective study conducted on type 2 diabetic patients from the ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
1
13
1
Order By: Relevance
“…The MPV was extensively studied as a diagnostic and prognostic tool in ACS [18], and furthermore has been proposed as a marker to guide utilization of abciximab in patients with acute MI [33]. Analogously, high MPV correlated with increased metabolic risks in our study and was recently shown to decline after glycemic control in diabetes [34]. HDL-C therefore possibly indicates the need for intensified antithrombotic treatment in the setting of stable CAD.…”
Section: Discussionsupporting
confidence: 65%
“…The MPV was extensively studied as a diagnostic and prognostic tool in ACS [18], and furthermore has been proposed as a marker to guide utilization of abciximab in patients with acute MI [33]. Analogously, high MPV correlated with increased metabolic risks in our study and was recently shown to decline after glycemic control in diabetes [34]. HDL-C therefore possibly indicates the need for intensified antithrombotic treatment in the setting of stable CAD.…”
Section: Discussionsupporting
confidence: 65%
“…However, multivariate analyses failed to find their associations with NTIS. Glycosylated hemoglobin A 1c (HbA 1c ) level can reflect the levels of blood glucose before and after the onset [41], but this study did not find an association between HbA 1c level and NTIS. The reason may be that NIHSS score and HbA 1c level could not reflect infarction volume and stress degree consistently.…”
Section: Discussioncontrasting
confidence: 59%
“…Mean platelet volume (MPV) is an indicator of platelet size and activity. Several studies have reported that MPV changes are associated with morbidity and mortality in patients with diseases such as sepsis, diabetes mellitus, myocardial infarction, and chronic inflammatory disorders [8][9][10][11] . Although there are several studies about the association of MPV with the diagnosis, morbidity, and mortality of COVID-19 patients, the results were contradictory [11][12][13][14] .…”
mentioning
confidence: 99%